Role of histone H1 in chromatin and gene expression in the african trypanosome : broad skills, specific functions? - Pena, Ana Catarina Dias, 1985- (2017)
Tese de doutoramento, Ciências Biomédicas (Microbiologia e Parasitologia), Universidade de Lisboa, Faculdade de Medicina, 2015